IMPLEMENTASI CONVOLUTIONAL NEURAL NETWORK MENGGUNAKAN RESNET 50 UNTUK MENGKLASIFIKASI TINGKAT KEMANTANGAN BUAH PEPAYA - Mellysa Pratama; Erwin Dwika Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Papaya is a very popular tropical fruit variety because it is rich in nutrients. However, the method of assessing the ripeness of papaya fruit is still often done manually, which can cause errors in the separation and distribution process. Thus, this study aims to develop an automatic system to classify the ripeness level of papaya fruit using the Convolutional Neural Network (CNN) method based on the ResNet50 architecture. The dataset used consists of papaya fruit images divided into four stages of ripeness, namely unripe, half-ripe, and unfit. The images then undergo a preprocessing process that includes resizing the image to 224 × 224 pixels, adjusting pixel values, and data augmentation through techniques such as rotation, zoom, and horizontal flipping to increase the variety of training data. The model is trained using a transfer learning approach by utilizing existing weights from the imagenet dataset. Model performance evaluation is carried out through the use of a confusion matrix and a classification matrix that includes accuracy, precision, recall, and F1 score. The results of the training process show that the model achieved a training accuracy of 91.72% and a validation accuracy of 83.56%, with a validation loss value of 0.4958. These findings indicate that the model can classify papaya fruit images with relatively good and consistent performance. This research is expected to support the automation process in identifying the ripeness level of papaya fruit in the agricultural and food industry sectors. Keywords: image classification, papaya, CNN, Resnet-50, deep learning.